Special issue introduction: Craft economies and inequalities. (December 2022) - Patel, Karen; Dudrah, Rajinder
Craft as a creative industry has received increased public, academic and policy attention in recent years. However, this tends to centre on a Westernised, white, middle-class version of craft practice associated with values of authenticity, the valorisation of the handmade, and 'hipster' culture. At the same time, despite a rich body of work on inequalities in the cultural industries, some of which is published in this journal, little attention has been given to craft. These matters are addressed in this special issue which interrogates the character and workings of the contemporary craft economy and provides much needed insight into experiences of inequality in the sector, drawing on research from the Global North and South. It also includes Cultural Commons contributions from Susan Luckman, Carol Tulloch and Saskia Warren which reflect on various aspects of contemporary craft.